Meatscapes: Spaces and processes associated to subsistence livestock - Farah, Leila (Cuizine, 2016)
How was subsistence livestock linked to architecture and the urban development in the settlement of 17th and 18th century Montreal? This article argues that landscapes and buildings interact with and accommodate the transformation of livestock products and by-products along various stages; and, that these animal parts contribute to defining urban landscapes. The paper presents a novel analytical framework to study foodscapes, and more particularly meatscapes by way of identifying spaces through which animal parts transited, and by spatially mapping them. It does so via a mixed methodological approach, including researching legal documents, travelers’ notes, databases, historical maps and plans dating back to the French period. Examining processes and spaces involving subsistence livestock, their products and by-products as well as individuals related to their transformation provides a new perspective on how ordinary activities shaped the lives and the spaces in a settlement.